Heterologous expression of Bromelain in Escherichia coli - M., Bala; Mohd. Salleh, Hamzah; Amid, Azura; Mel, Maizirwan; Jami, Mohammed Saedi (2011)
In spite of the fact that commercial bromelain supplements are available in the market, to date, none of them are produced and formulated from recombinant forms. They are extracted and purified (often partially) from the stem and fruit of pineapple. This makes the production of bromelain very difficult, less reliable, often contaminated and expensive. In this study, a recombinant bromelain from BL21 A clone was expressed as soluble and insoluble active enzyme. Maximum activity was observed at 4-hour post induction with 0.2% L-arabinose and over 60% of the enzyme was found to be expressed in soluble form. The enzyme fractions were purified using Nickel-NTA spin column. Purification fold and % yield of the purified lysate were found to be 35 and 75% respectively. SDS-PAGE results showed that the purified bromelain exhibited a single band with molecular weight of about 45kDa.